Web services theory and practice - Guruge, Anura (Burlington, MA : Digital Press, 2004)
This is a soup-to-nuts reference guide on all aspects of Web Services - where Web Services is a fast emerging set of Internet-specific middleware technology to further promote the growth of all aspects of e-business via standardization, collaboration and "franchising." This book is best characterized as an executive brief for IT and senior management rather than a nuts-and-bolts technical guide for portal implementers. Think of it as the "Cliffs Notes on Web Services." Given this audience, the book consistently focuses on business needs, value propositions, ROI, proven solutions and actual examples of current implementations. Each chapter also ends with a 10-item "Q & A" section that consolidates and summarizes the information discussed in the chapter. The book is illustrated with detailed technical diagrams, includes lots of arresting subtitles and contains many bullet lists and tables to facilitate (and encourage) productive skimming. Decision makers - the intended readership for this book - gain increasing comfort and confidence as they get into the book that they are getting to see all facets of the issues, on a consistent basis, and that they will not be blind-sided at meetings by people asking 'difficult' questions. At the end of each chapter, Guruge summarizes and reinforces key points, allowing the reader to skim through the topics for crucial information. The book also leverages living outside resources and ensures that the readership always has ready and consistent access to any and all terms, definitions and concepts they might not be familiar with. "Debate style" presentation, focusing repeatedly on pros-and-cons, e.g., .NET vs. Java, open vs. proprietary and buy vs. build Author's trademark detailed architectural and network diagrams of portal implementations Q & A section at end of each chapter.
Web services : what, why, and where? -- XML, the backbone of Web services -- Microsoft's Web services -- Universal description, discovery, and integration -- Soap -- Java and Web services -- Deploying and managing Web services -- Taking stock of Web services.
Includes bibliographical references (p. 355) and index.
Keywords: Web services; Electronic books